Effect of TraÄ±nÄ±ng and Competence on MotÄ±vatÄ±on wÄ±th Cultural OrganÄ±zatÄ±on as MedÄ±atÄ±on (Research of SMEs Entrepreneurs Women In East Java, Indonesia) - Astutiningsih, Sri Eka; Troena, Eka Afnan; Thoyib, Armanu; Setiawan, Margono (APMBA (Asia Pacific Management and Business Application), 2016)
This study aim is to analyze the effect of training and competence on motivation of women entrepreneurs with mediation of organizational culture which has been rarely studied. This research will fill this gap by conducting research on women entrepreneurs in Indonesia. The uniqueness of this study is the first study to examine micro and small women entrepreneurs in East Java, Indonesia. The samples are 100 respondents. Data was collected by questionnaire that measured by 5-point Likert scale. The data obtained isÂ  analyzedby path analysis with SPSS version 21 software.The results showed that the training and competence directly have positive and significant effects on organizational culture. The results also indicate that training, competencies and organizational culture directly have positive and significant effects on motivation of female entrepreneurs.The calculation of the indirect effect indicate that organizational culture mediates the effect of training and competence on motivation of female entrepreneursÂ